Pengaruh Lingkungan Kerja dan Kompensasi terhadap Kepuasan Kerja Karyawan PT Periska Multi Usaha Madiun - Dwi Ayu Mustikaningsih; Sulastri Irbayuni (Universitas Batanghari, 2022)
This study aims to determine the influence of the work environment and competence on the job satisfaction of employees of PT Periska Multi Usaha Madiun. This research included a quantitative study using a saturated sample technique of 52 employees of the cathering section of PT Periska Multi Usaha Madiun. The method of data collection is through a questionnaire that is distributed to employees of the cathering department of PT Periska Multi Usaha Madiun. The variables set by the researcher include: independent variables, namely work environment (X1), compensation (X2), and dependent variables, namely Job Satisfaction (Y). Technical analysis uses the Partial Least Square (PLS) model to construct a model that can be assumed when there are several factors. The findings show that the high level of work environment and compensation can increase job satisfaction of employees of PT Periska Multi Usaha Madiun.